Computer vision with OpenCV 3 and Qt5 : build visually appealing, multithreaded, cross-platform computer vision applications /: build visually appealing, multithreaded, cross-platform computer vision applications. (2018) - Ahmadi Tazehkandi, Amin
No abstract available